2017
DOI: 10.1183/13993003.00451-2017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of inhaled corticosteroids on sputum bacterial and viral loads in COPD

Abstract: Inhaled corticosteroid-containing medications reduce the frequency of COPD exacerbations (mainly infectious in origin) while paradoxically increasing the risk of other respiratory infections The aim was to determine the effects of inhaled corticosteroids on airway microbial load in COPD patients and evaluate the influence of the underlying inflammatory profile on airway colonisation and microbiome.This is a proof-of-concept prospective, randomised, open-label, blinded endpoint study. Sixty patients with stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(156 citation statements)
references
References 34 publications
6
133
2
5
Order By: Relevance
“…ICS use in asthma and COPD is associated with an increased risk of upper respiratory tract infections [10,11]. In people with COPD, ICS use is associated with a higher prevalence of pneumonia [12] and a change in the lung microbiome, although not a change in respiratory virus detection [13]. The evidence in asthma is less clear cut, but at least one observational study has shown an increased risk of pneumonia or lower respiratory infection [14].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…ICS use in asthma and COPD is associated with an increased risk of upper respiratory tract infections [10,11]. In people with COPD, ICS use is associated with a higher prevalence of pneumonia [12] and a change in the lung microbiome, although not a change in respiratory virus detection [13]. The evidence in asthma is less clear cut, but at least one observational study has shown an increased risk of pneumonia or lower respiratory infection [14].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…The field of microbiome research in bronchiectasis is less advanced than the field of other respiratory diseases such as cystic fibrosis and chronic obstructive pulmonary disease (COPD), with fewer published studies [33][34][35][36]. Nevertheless, evidence to date suggests remarkable consistency in findings across supposedly distinct disease entities [37][38][39][40]. The first group of published bronchiectasis microbiome studies have supported the findings of culture-based studies, identifying genera associated with infection such as Haemophilus, Streptococcus and Pseudomonas, while also providing evidence of bacterial pathogens in culture-negative patients [41][42][43].…”
Section: Bronchiectasis Microbiome Versus Culturementioning
confidence: 99%
“…Additional analyses were as follows: (i) the correlation among distinct symptom domains/use of rescue medications; (ii) the correlation of FeNO levels and symptom scores; and (iii) the correlation of lung function with airway inflammation and symptom scores. A post hoc analysis was performed to specifically evaluate correlations between symptom scores and sputum inflammatory cell counts in the subpopulation of COPD patients with sputum eosinophils ≥2% (Appendix S1, Supplementary Information).…”
Section: Methodsmentioning
confidence: 99%